The reality of tourism culture in Algerian society _Field Study In Batna _ - medyaza, tarek; ikdoumi, hanan (Journal of Social Sciences and Humanities, 2024)
Tourism awareness is essential for the development of tourism that meets the aspirations and objectives of the Algerian State.In addition to the attention paid by the Algerian State to the material investment aspect, greater attention must be paid to the human race, not only those working in the tourism sector but also all of society. From this absolute point of view, we have tried to shed light on the role of community culture in shaping tourism awareness. We have studied the field of Batna, where our research has been divided into a theoretical section in which we have looked at what we have found to be important for our study, a field segment in which we have presented our observations, the format, interviews and findings, as well as suggestions and recommendations.